THE IMPLEMENTATION OF PROGRESSIVE LAW AGAINST THE DEFENDANT ABILITY TO ACHIEVE SUBSTANTIVE JUSTICE - Rr. Dijan Widijowati (UNISSULA, 2021)
The enactment of the law in society aims to create justice, legal certainty, benefit and social empowerment for the community, to lead to the ideals of the court as a protector of society, the judge must always prioritize the 4 (four) legal objectives above in every decision he makes. This is in line with what the law is based on, namely the law for the welfare of the community. The poor are often victims of unfair law enforcement due to their ignorance of law enforcement and financial incompetence. The purpose of this study is to analyze the progressive law applied to poor defendants seeking substantive justice and to find out and analyze the state should be able to assist poor defendants in the judicial process in accordance with the rule of law principle. This research uses normative juridical method. Judges in deciding legal cases for the poor should have a progressive view, thus judges will conceptualize each article in the legislation not only as a statement about the existence of a causal (cause and effect) relationship that is straightforward according to logical law but also always contains moral substance originating from ethics and professionalism of judges.